Human Umbilical Cord Mesenchymal Stem Cells Inhibit Pyroptosis of Renal Tubular Epithelial Cells through miR-342-3p/Caspase1 Signaling Pathway in Diabetic Nephropathy - Shuo Zheng; Ke Zhang; Yaqi Zhang; Jing He; Yu Ouyang; Ruibo Lang; Chunchun Ao; Yijia Jiang; Huan Xiao; Yu Li; Mao Li; Changyong Li; et al. (Hindawi Limited, 2023)
Diabetic nephropathy (DN) is one of the microvascular complications of diabetes. Recent studies suggest that the pyroptosis of renal tubular epithelial cell plays a critical role in DN. Currently, effective therapeutic strategies to counteract and reverse the progression of DN are lacking. Mesenchymal stem cells (MSCs) represent an attractive therapeutic tool for tissue damage and inflammation owing to their unique immunomodulatory properties. However, the underlying mechanisms remain largely unknown. In the present study, we found that human umbilical cord MSCs (UC-MSCs) can effectively ameliorate kidney damage and reduce inflammation in DN rats. Importantly, UC-MSC treatment inhibits inflammasome-mediated pyroptosis in DN. Mechanistically, we performed RNA sequencing and identified that miR-342-3p was significantly downregulated in the kidneys of DN rats. Furthermore, we found that miR-342-3p was negatively correlated with renal injury and pyroptosis in DN rats. The expression of miR-342-3p was significantly increased after UC-MSC treatment. Moreover, miR-342-3p decreased the expression of Caspase1 by targeting its 3'-UTR, which was confirmed by double-luciferase assay. Using miRNA mimic transfection, we demonstrated that UC-MSC-derived miR-342-3p inhibited pyroptosis of renal tubular epithelial cells through targeting the NLRP3/Caspase1 pathway. These findings would provide a novel intervention strategy for the use of miRNA-modified cell therapy for kidney diseases.